Development of spring durum wheat cultivars resistant to stem rust in Western Siberia - V. S. Yusov; M. G. Evdokimov; L. V. Meshkova; D. A. Glushakov (Труды по прикладной ботанике, генетике и селекции, 2021)
Background. Stem rust of wheat, caused by the biotrophic fungus Puccinia graminis Pers. f. sp. tritici Eriks. et Henn., is a dangerous disease that afflicts serious economic damage to the cultivation of durum wheat.Materials and methods. Cultivars and promising materials developed at the Spring Durum Wheat Breeding Laboratory, Omsk Agrarian Scientific Center (OASC), lines obtained under the CIMMYT and KASIB programs, and accessions from the VIR collection were the objects of research. Field experiments, phenological observations, and assessment of stem rust resistance were carried out from 1990 through 2019 in the OASC experimental fields using conventional methods. Resistance to the Ug99 race was evaluated under natural infection pressure at the Kenya Agricultural and Livestock Research Organization (KALRO).Results. Promising source material was identified and included in the Laboratory’s breeding program. The ways were shown to develop stable cultivars of spring durum wheat for the environments of Western Siberia. A strategy was proposed for the selection of genotypes in hybrid combinations of spring durum wheat: it would include early selection (starting from F2) for disease resistance with simultaneous screening for quantitative traits and pasta-making qualities. The description and advantages of cv. ‘Omsky korall’, submitted to the State Variety Trials in 2018, are presented. This cultivar combines high yield, adaptability, resistance to the local population and the Ug99 race of the stem rust pathogen, and excellent pasta-making qualities.Conclusion. As a result of these studies under heavy stem rust pressure in Western Siberia, all breeding nurseries obtained source material resistant to the Omsk population of P. graminis. The released cultivars ‘Omskaya yantarnaya’ and ‘Omsky izumrud’ demonstrate resistance to the Omsk population of the stem rust causative agent.